THE SPECIFICS AND WAY OF ATRIOVENTRICULAR BLOCK COURSE IN INFANTS MYOCARDITIS - E. S. Vasichkina; N. M. Lyuskina; T. M. Pervunina; D. S. Lebedev (Российский кардиологический журнал)
Aim. To study the specifics of clinical course and outcomes of higher degree AVB, developed due to inflammatory changes of myocardium in infants, during three years follow-up.Material and methods. For the assessment of AVB specifics in current myocarditis we have summarized the investigation data of 6 patients younger than 1,5 y. o.; mean age 10,0±4,5 months (3 to 16 months). In all clinical cases we performed the analysis of medical source documents with outcopying of pregnancy data, analysis of cardiotocography (CTG) data and ultrasound examination (USE) of the fetus (to rule out inborn cause for AVB), stages of the growth and development of a child, diseases anamnesis. The complex laboratory and instrumental investigation was done, including evaluation of biochemical markers of inflammation and serum markers of myocardial damage, electrocardiographic (ECG) and echocardiographic (EchoCG) studies.Results. Mean follow-up was 23,3±10,4 months (from 9 to 35 months). On treatment, all patients had tendency for the decrease of cardiac specific enzymes, the decrease of heart failure functional class and positive EchoCG dynamics by the end of the first year. However, AV-conduction disorders of the heart in all patients had irreversible course. Permanent pacemaker (PPM) was set up in two cases, in 6 and 14 months after diagnosis.Conclusion. In infants the AV conduction disorders that develop in myocarditis, show irreversible pattern of clinical course.